ANALISIS USAHA PENGOLAHAN AMPLANG CINDY IKAN BANDENG (Chanos chanos) DI DESA SUNGAI MERIAM KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Gustin Patiku; Helminuddin; Oon Darmansyah (2339-1324, 2023)
This study aimed to explain the advantages of the Cindy Milkfish Amplang Processing Business in Sungai Meriam Village, Anggana Sub-district and to find out the feasibility of the Cindy Milkfish Amplang Processing Business in Sungai Meriam Village based on the criteria of RCR, Break-Even Point (BEP), Payback Period (PP) and Returns On Investment (ROI) as well as to know the Driving and Inhibiting Factors for the Cindy Milkfish Amplang Processing Business in Sungai Meriam Village, Anggana Sub-district. The research was carried out from March 2021 to February 2022 in Sungai Meriam Village, Sub-district. The research method and data collection used was a census with a sample of 1 respondent. The results showed that Cindy's amplang processing business in Sungai Meriam Village benefited from a kentngan value of Rp. 29,134,476 / month (6 times production). Furthermore, the Cindy Milkfish Amplang Processing Business is economically viable with RCR value of 1.9, the Break-Even Point (BEP) value from BEP Price of Rp.10,289/pack, the amount of BEP Production is1,543 kg/production and the amount of BEP Sales is Rp. 2.750,096 /month, the Payback Period (PP) is 2,3 months or 70 days and Return On Investment (ROI) is 20,88%. It is found that the driving factor for the business owner is having attended training or seminars held by the Department of Industry, whereas the inhibiting factor is seasonal raw fish materials, non-maximum marketing in various media, processing workers who often change in every production